1981
DOI: 10.2466/pms.1981.52.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Correlates of the Rod-and-Frame Test

Abstract: 38 right-handed children in sixth grade (17 boys and 21 girls) were administered the WISC Block Design to reflect activity of the right hemisphere of the brain and two versions (verbal and nonverbal) of the Rod-and-frame Test, a measure of field dependence/independence. The Pearson product-moment correlations showed a significant negative correlation between the traditional verbal administration of the Rod-and-frame Test and the WISC Block Design only for the 17 boys. The nonverbal procedure used to administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…These results fit in well with the findings of Brugger and Baumann (1994), which demonstrate that believers in paranormal phenomena cannot generate random numbers as well as skeptics. Apart from these considerations, the already mentioned hemispheric asymmetry which was found for field dependents (Berlin & Languis, 1981) and believers in psi (Brugger et al, 1993) could also contribute to the current findings.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…These results fit in well with the findings of Brugger and Baumann (1994), which demonstrate that believers in paranormal phenomena cannot generate random numbers as well as skeptics. Apart from these considerations, the already mentioned hemispheric asymmetry which was found for field dependents (Berlin & Languis, 1981) and believers in psi (Brugger et al, 1993) could also contribute to the current findings.…”
Section: Discussionsupporting
confidence: 56%
“…Because it has been suggested that field dependence is also associated with hemispheric asymmetry (Berlin & Languis, 1981;Pizzamiglio & Carli, 1974;Waber, 1977;Witkin et al, 1971), this is cited as a further argument that there exists an association between field dependence and belief in paranormal phenomena.…”
Section: Field Dependencementioning
confidence: 99%
“…And indeed, a comparison of the mean errors reported in studies of older adults on 2D tests (Gruenfeld & MacEachron, 1975;Robert & Tanguay, 1990) with the VERF suggests that the mean degrees of error in this study (12.55 ) represents an increase relative to 2D RFTs. Gruenfeld These findings extend previous research on the relationship between 2D RFTs and tests of spatial ability (e.g., Berlin & Languis, 1981;Dor-Shav, 1984;Fowler & Fowler, 1984;Shore & Carey, 1984;Tramer & Schludermann, 1974) to a 3D RFT. Interestingly, there was little difference in the magnitude of the correlations of AD with various measures of spatial ability.…”
Section: Discussionsupporting
confidence: 76%
“…However, the RFT has also been considered to be a test of spatial ability in which participants must perceive spatial relationships relative to their own bodies, ignoring distracting stimuli (Linn & Petersen, 1985; VIRTUAL ENVIRONMENT ROD AND FRAME TEST 1171 Voyer et al, 1995). As 2D RFTs have consistently demonstrated relationships with other tests of spatial ability (e.g., Berlin & Languis, 1981;Dor-Shav, 1984;Fowler & Fowler, 1984;Shore & Carey, 1984;Tramer & Schludermann, 1974), a valid 3D RFT would be expected to do likewise.…”
mentioning
confidence: 93%
“…They are also more accurate on measures of spatial ability such as mental rotation (Johnson and Meade 1987;Kerns and Berenbaum 1991;Masters and Sanders 1993) and spatial visualization (Kerns and Berenbaum 1991). Finally, males score higher on the Embedded Figures Test (EFT) (Berlin and Languis 1981;Nebot 1988;Witkin et al 1962), which measures attention to detail and field independenceconsidered to be prerequisites for systemizing (BaronCohen 2002).…”
Section: Sex Differences In Empathizing and Systemizingmentioning
confidence: 97%